Hedgehog signaling is a promising target for the treatment of hepatic fibrogenesis: a new management strategy using itraconazole-loaded nanoparticles - Elmorsy, Elsayed A.; Saber, Sameh; Kira, Ahmed Y.; Alghasham, Abdullah; Abdel-Hamed, Mohamed R.; Amer, Maha M.; Mohamed, Enas A.; AlSalloom A., A; Alkhamiss, Abdullah S.; Hamad, Rabab S.; Abdel-Reheim, Mustafa Ahmed; Ellethy, Abousree T.; et al. (Frontiers in Pharmacology, 2024)
Liver fibrosis is a disease with a great global health and economic burden. Existing data highlights itraconazole (ITRCZ) as a potentially effective anti-fibrotic therapy. However, ITRCZ effect is hindered by several limitations, such as poor solubility and bioavailability.This study aimed to formulate and optimize chitosan nanoparticles (Cht NPs) loaded with ITRCZ as a new strategy for managing liver fibrosis. ITRCZ-Cht NPs were optimized utilizing a developed 2 2 full factorial design. The optimized formula (F3) underwent comprehensive in vitro and in vivo characterization. In vitro assessments revealed that F3 exhibited an entrapment efficiency of 89.65 ± 0.57%, a 169.6 ± 1.77 nm particle size, and a zeta potential of +15.93 ± 0.21mV. Furthermore, in vitro release studies indicated that the release of ITRCZ from F3 adhered closely to the first-order model, demonstrating a significant enhancement (p-value < 0.05) in cumulative release compared to plain ITRCZ suspension. This formula increased primary hepatocyte survival and decreased LDH activity in vitro. The in vivo evaluation of F3 in a rat model of liver fibrosis revealed improved liver function and structure. ITRCZ-Cht NPs displayed potent antifibrotic effects as revealed by the downregulation of TGF-β, PDGF-BB, and TIMP-1 as well as decreased hydroxyproline content and α-SMA immunoexpression. Anti-inflammatory potential was evident by reduced TNF-α and p65 nuclear translocation. These effects were likely ascribed to the modulation of Hedgehog components SMO, GLI1, and GLI2. These findings theorize ITRCZ-Cht NPs as a promising formulation for treating liver fibrosis. However, further investigations are deemed necessary.